HDAC-6 interacts with and deacetylates tubulin and microtubules in vivo - Zhang, Yu (Oxford University Press, 2003)
Microtubules are cylindrical cytoskeletal structures found in almost all eukaryotic cell types which are involved in a great variety of cellular processes. Reversible acetylation on the ε-amino group of α-tubulin Lys40 marks stabilized microtubule structures and may contribute to regulating microtubule dynamics. Yet, the enzymes catalysing this acetylation/deacetylation have remained unidentified until recently. Here we report that β-tubulin interacts with histone deacetylase-6 (HDAC-6) in a yeast two-hybrid assay and in vitro. We find that HDAC-6 is a micro tubule-associated protein capable of deacetylating α-tubulin in vivo and in vitro. HDAC-6’s microtubule binding and deacetylation functions both depend on the hdac domains. Overexpression of HDAC-6 in mammalian cells leads to tubulin hypoacetylation. In contrast, inhibition of HDAC-6 function by two independent mechanisms—pharmacological (HDAC inhibitors) or genetic (targeted inactivation of HDAC-6 in embryonic stem cells)—leads to hyperacetylation of tubulin and microtubules. Taken together, our data provide evidence that HDAC-6 might act as a dual deacetylase for tubulin and histones, and suggest the possibility that acetylated non-histone proteins might represent novel targets for pharmacological therapy by HDAC inhibitors.